2019
DOI: 10.1002/cpdd.757
|View full text |Cite
|
Sign up to set email alerts
|

Lack of Effect of Rezafungin on QT/QTc Interval in Healthy Subjects

Abstract: Rezafungin is a new echinocandin in development for treatment of candidemia and invasive candidiasis,and for prophylaxis of invasive fungal infections. Rezafungin is the first echinocandin to undergo definitive QT/QTc study. This phase 1, single-center, randomized, double-blind trial was conducted to assess effects of intravenous rezafungin vs intravenous placebo (with moxifloxacin as positive control) on the QT interval of the electrocardiogram, corrected for heart rate by Fridericia's formula (QTcF), in heal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 22 publications
0
10
0
Order By: Relevance
“…Preclinical studies have established the efficacy of RZF in animal models of candidemia, IC, and Candida biofilms [ 5 , 9 , 12–15 ]. In addition, phase 1 studies have demonstrated the safety and tolerability of RZF in healthy volunteers [ 11 , 16 ]. Here we present the results of STRIVE, a phase 2 trial designed to evaluate the safety and efficacy of intravenous (IV) RZF, compared with caspofungin (CAS) and optional oral fluconazole stepdown therapy, in the treatment of candidemia/IC.…”
mentioning
confidence: 99%
“…Preclinical studies have established the efficacy of RZF in animal models of candidemia, IC, and Candida biofilms [ 5 , 9 , 12–15 ]. In addition, phase 1 studies have demonstrated the safety and tolerability of RZF in healthy volunteers [ 11 , 16 ]. Here we present the results of STRIVE, a phase 2 trial designed to evaluate the safety and efficacy of intravenous (IV) RZF, compared with caspofungin (CAS) and optional oral fluconazole stepdown therapy, in the treatment of candidemia/IC.…”
mentioning
confidence: 99%
“…In addition, a randomized, double-blind, phase I study was conducted in healthy volunteers to evaluate cardiac effects of single doses of intravenous rezafungin [ 203 ]. For echinocandins, data on QT prolongation among echinocandins are limited.…”
Section: Antifungal Drugs In Clinical Developmentmentioning
confidence: 99%
“…An additional phase 1 study has shown no effect on QTc or other aspects of the cardiac electrical rhythm (Flanagan et al, 2020).…”
Section: Clinical Datamentioning
confidence: 96%
“…This data has subsequently been used to develop a population level PK model ( Lakota et al., 2018 ). An additional phase 1 study has shown no effect on QTc or other aspects of the cardiac electrical rhythm ( Flanagan et al., 2020 ).…”
Section: Rezafungin (Cidara)mentioning
confidence: 99%